From Dissent to Terrorism: The Formation of a Security Grammar in Malaysia - Abdul Hamid, Haezreena Begum binti, Dr (Indonesia Law Review, 2026)
The absence of a universally accepted definition of terrorism has enabled states to exercise wide discretion in naming, governing, and exceptionalising violence. This article argues that, in Malaysia, “terrorism” did not emerge as a neutral legal category but as the product of a historically evolving security grammar, a patterned way of interpreting ideology, dissent, and conflict through the lens of existential threat. Employing a qualitative doctrinal socio-legal methodology, the study integrates analysis of international and Malaysian legal frameworks with case-based examination of key episodes, including Memali, Al-Arqam, Al-Ma’unah, Lahad Datu, and ISIS-linked incidents. Statutes, judicial decisions, policy materials, and regional case studies are analysed thematically to trace how definitional ambiguity is translated into concrete legal practice. The findings demonstrate that Malaysia’s counter-terrorism regime was shaped prior to modern terrorism statutes through practices of preventive governance that rendered belief and association governable through exception. These early patterns were later consolidated within contemporary legal architecture and globalised through transnational jihadist networks. The article shows how heterogeneous conflicts whether religious dissent, territorial disputes, or political mobilisation are converted into “terrorism,” activating exceptional powers and displacing alternative political or historical frames. By theorising terrorism as a legal and epistemic construction, this study reveals how counter-terrorism in Southeast Asia operates through a security grammar that prioritises pre-emption over proof and deterrence over proportionality. It highlights the enduring implications of this logic for legality, accountability, and human rights.